The accepted narrators who were weak in them because of their sheikhs in Ibn Uday's book Al-Kamil - An inductive and analytical study - Latif, Anwar Mahmoud; Bouneama, Fouad (Journal of Islamic Sciences, 2023)
This study reveals the accepted narrators who were weak in them because of their sheikhs in the book Al-Kamil in the weak men of Ibn Adi, with a brief translation of them, in which their sheikhs and students are mentioned, and who are the sheikhs who were weak in the narrator because of them, with an indication of the number of narrations of each narrator in the books of the year that stood On it with reference to its sources, and the research problem lies in the fact that the trustworthy narrator, if he narrated from a trustworthy narrator, then the scholars accept his hadith, but if the trustworthy narrator narrated from a weak narrator; He may speak about this narrator because of his narration from the weak, and the defect in the narration is on the side of the weak, not trustworthy. The narrator is from the collection of sayings, and the importance of the research is due to the fact that it deals with a problem of the problems of narrations with chains of transmission in which acceptable narrators were weak in them because of the narration of weak sheikhs, and it facilitates access to the accepted narrators who were weak in them because of their sheikhs in the book of Al-Kamil by collecting them in this research, and it became clear to the researcher after Induction is that the number of these narrators in the book in question is )eight narrators), are in the rank of sadooq, or sadooq who has illusions.
Keywords: Ibn Uday; Al-Kamil; Narrators; Trustworthy Narrators; Sheikhs